Amo Ergo Sum — I love, Therefore, I am – Emotional Synchrony: A Norris’ Method of Concept Clarification - Tuppal, Cyruz P.; Ninobla, Marina Magnolia G.; Ruiz, Mara G.; Loresco, Richard C.; Reñosa, Mark Donald C. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Nursing is an interpersonal process that requires a deeper emotive-caring and communion-encounter with a higher degree of emotional synchrony. However, the social, cultural, ethical, economic, legal, and technological demands make it intangible and indefinable.Purpose: To identify and delineate the antecedents, defining attributes, and outcomes of emotional synchrony using both empirical and theoretical literature.Methods: This concept analysis used the Norris’ method of concept clarification. Electronic databases such as OVID, Web of Science, CINHAL, PsychInfo, SocIndex, PubMed, and ProQuest were used to search the keyword ‘emotional synchrony.’ There were fifty-two sources included in the inductive thematic analysis to identify, analyze, recognize, and report the themes generated from the corpus. The discussion is grounded in light of the Theory of Nursing as Caring to elucidate its utility within the parlance of nursing as caring.Results: The Model of Patterning Emotional Synchrony offers a new perspective toward a meaningful synchronous experience in the communion of beings that illuminates a soul-felt connectedness through the encounter, presence, and bond. The emotional synchrony’ is a phenomenon of caring integration where an intricate dance through a triadic-synchronistic rhythm of fusion, attunement, and effervescence contribute to the personhood, growth in reflection, and capacity to care. Also, as the emotional synchrony becomes an outward expression of caring, and as a manifestation of healing-caring-moment, the person embodies caring as a mode of being and views all persons as caring.Conclusion: The model explicates that it is the emotional synchrony where the person develops a soul-felt connection with others. It is with emotional synchrony that refuels the synergy and transcendence towards a communion of beings to embody Amo Ergo Sum—I love. Therefore, I am.